Biventricular Longitudinal Strain Predict Mortality in COVID-19 Patients - Xie, Yuji; Wang, Lufang; Li, Meng; Li, He; Zhu, Shuangshuang; Wang, Bin; He, Lin; Zhang, Danqing; Zhang, Yongxing; Yuan, Hongliang; Wu, Chun; Sun, Wei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Biventricular longitudinal strain has been recently demonstrated to be predictive of poor outcome in various cardiovascular settings. Therefore, this study sought to investigate the prognostic implications of biventricular longitudinal strain in patients with coronavirus disease 2019 (COVID-19). Methods: We enrolled 132 consecutive patients with COVID-19. Left ventricular global longitudinal strain from the apical four-chamber views (LV GLS4CH) and right ventricular free wall longitudinal strain (RV FWLS) were obtained using two-dimensional speckle-tracking echocardiography. Results: Compared with patients without cardiac injury, those with cardiac injury had higher levels of coagulopathy and inflammatory biomarkers, higher incidence of complications, more mechanical ventilation therapy, and higher mortality. Patients with cardiac injury displayed decreased LV GLS4CH and RV FWLS, elevated pulmonary artery systolic pressure, and higher proportion of pericardial effusion. Higher biomarkers levels of inflammation and cardiac injury, and the presence of pericardial effusion were correlated with decreases in LV GLS4CH and RV FWLS. During hospitalization, 19 patients died. Compared with survivors, LV GLS4CH and RV FWLS were impaired in non-survivors. At a 3-month follow-up after discharge, significant improvements were observed in LV GLS4CH and RV FWLS. Multivariate Cox analysis revealed that LV GLS4CH (hazard ratio: 1.41; 95% confidence interval [CI]: 1.08 to 1.84; P = 0.011) and RV FWLS (HR: 1.29; 95%CI: 1.09 to 1.52; P = 0.003) were independent predictors of higher mortality in patients with COVID-19. Conclusions: LV GLS4CH and RV FWLS are independent and strong predictors of higher mortality in COVID-19 patients and can track improvement during the convalescent phase of their illness. Therefore, biventricular longitudinal strain may be crucial for risk stratification and serial follow-up in patients with COVID-19.